CULTURAL HERITAGE ASSETS CHARACTERISTICS AND ACCOUNTING COORDINATES - IULIANA CENAR; ELENA-DANIELA CRIȘAN (SPĂTĂCEAN) (Annals of the University of Petrosani: Economics)
Although many researchers and various international standardization bodies, over the past twenty years, have focused their efforts on the search for appropriate accounting treatments, goods of historical and cultural interest bring and discuss a number of issues, given their peculiarities that assume the complementarity of economic aspects with historical, cultural ones, with the need to preserve the identity of a nation. The paper outlines an overview of heritage assets according to the national legislative framework and IPSAS 17, captures elements of their idividualization, as well as problems regarding their assessment and recognition in the financial statements.